Formy świadczeń oraz systemy finansowania polityki społecznej w krajach europejskich - Raczkowska, Małgorzata (Forms of Benefits and Systems For Financing Social Protection in European Union Countries, 2009)
The paper analyzes the forms of benefits and systems for financing social protection in European Union countries. Research includes European Union countries and European Free Trade Association countries (EFTA) - Iceland, Norway, and Switzerland. In a social benefits structure the majority of the benefits are those paid in cash - more than 65% of the average amount. Different countries have markedly different systems for financing social protection, depending on whether they favour social security contributions (59.0% of total receipts at EU-27 level in 2005) or general government funding (37.6%)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 262-270